Factors Associated With Social Isolation Among the Older People in India. (September 2018) - Kotian, Devaki B.; Mathews, Maria; Parsekar, Shradha S.; Nair, Suma; Binu, V. S.; Subba, Sonu Hangma
Objective: To explore the factors associated with social isolation among older people using the data from Building Knowledge Base on Population Ageing in India (BKPAI) survey. Methods: Multiple logistic regression and classification and regression tree (CART) analysis were used to identify the factors associated with social isolation using data from BKPAI survey. An individual was regarded as socially isolated if the response was "never" to all 4 activities in the last 12 months: (1) attending public meeting, (2) attending any group/club/organizational meeting, (3) attending any religious program, and (4) visiting friends or relatives. Results: Among 9836 older people, 19.7% were observed to be socially isolated. From multiple logistic regression, age (odds ratio [OR] = 1.85 for age 80 to 89 years and OR = 2.67 for age ≥90), religion (OR = 0.54 for Christians compared to Hindus), duration of stay in current home (OR = 0.64 for 6-10 years compared to >10 years of stay), number of activities of daily living (ADLs) for which the assistance was needed (OR = 2.09 for 1 or 2, OR = 3.14 for 3 or 4, and OR = 12.05 for 5 or 6), and Alzheimer's disease (OR = 1.65) were identified as factors associated with social isolation. Number of ADL for which the assistance was needed and self-reported health status were the factors identified through CART analysis. Discussion: Requiring help in performing ADL, advancing age, and Alzheimer's disease were the likely factors for socially isolation among elderly patients in this surveyed population.